2009
DOI: 10.4062/biomolther.2009.17.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Dose Toxicity Test of Low Molecular Weight Fucoidan in Rats

Abstract: -The object of this study was to evaluate the single oral dose toxicity of Low Molecular Weight Fucoidan (LMF) in male and female rats. LMF was administered to female and male SD rats as an oral dose of 2,000, 1,000 and 500 mg/kg (body wt.). Animals were monitored for the mortality and changes in body weight, clinical signs and gross observation organ weight and histopathology of 14 principle organs were examined upon necropsy. As the results, no LMF treatment related mortalities, clinical signs, changes on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, we also found that its molecular weight was 1288.81 ± 62.55 kDa, which indicates a high molecular weight. In 2009, Yoon showed that fucoidan can be divided into low (< 10 kDa), medium (10–10,000 kDa) and high (> 10,000 kDa) molecular weights [ 33 ]. This molecular weight falls within the range of (10–10,000 kDa) mid-molecular-weight fucoidan [ 34 ], and low-molecular-weight fucoidan has better biological activity and it is easier to develop into anticancer drugs [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, we also found that its molecular weight was 1288.81 ± 62.55 kDa, which indicates a high molecular weight. In 2009, Yoon showed that fucoidan can be divided into low (< 10 kDa), medium (10–10,000 kDa) and high (> 10,000 kDa) molecular weights [ 33 ]. This molecular weight falls within the range of (10–10,000 kDa) mid-molecular-weight fucoidan [ 34 ], and low-molecular-weight fucoidan has better biological activity and it is easier to develop into anticancer drugs [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the edematous changes in uterus were considered as secondary changes from different physiological estrus cycles (32 , 33) . In addition, most of them were also rarely but generally observed as sporadic accidental findings in rodent toxicity studies (5 , 23 , 24) .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were conducted using SPSS for Windows (Release 14.0K, SPSS Inc., USA) and a p -value of less than 0.05 was considered to be a significant difference. In addition, degree of clinical signs, gross and histopathological findings were subdivided into 3 degrees: 3+ Severe, 2+ moderate, 1+ slight, according to the previous reports (5 , 23 , 24) .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the dosage volume was selected as 10 ml/kg, the recommended oral dose volume in rat (Flecknell, 1996) and the highest dosages, 2,000 mg/kg was selected based on the results of rat single dose toxicity test (Yoon et al, 2009), in which no noticeable toxicities were detected up to 2,000 mg/kg of dose levels in the both female and male rats, and 1,000 and 500 mg/kg were selected as middle and low dosages using common ratio 2 according to KFDA Guidelines (2005). In addition each female and male vehicle controls were added.…”
Section: Discussionmentioning
confidence: 99%
“…Although preclinical studies using HMF have been performed (Li et al, 2005); up to now, no detailed toxicological assessment of LMF has been reported except for mouse and rat single oral dose toxicity (Jung et al, 2008;Yoon et al, 2009). Therefore, the primary safety information after 14-day repeat oral treatment of LMF, obtained by acid hydrolysis of HMF from brown seaweed according to a previously published protocol (Nardella et al, 2000;Jung et al, 2007) were evaluated using rats, to determine the highest dosage for further 4-week repeated dose toxicity test and further clarity their safety for clinical use.…”
Section: Introductionmentioning
confidence: 99%